Sintesis Lapis Tipis SrTiO3 dengan Metode Solvotermal - Melvi Muharmi; Yulia Eka Putri; Diana Vanda Wellia (Jurnal Kimia Unand, 2022)
SrTiO3 thin layer were synthesized through solvothermal method by using FTO (fluorine-doped tin oxide) glass as a conductive substrate. The raw materials strontium nitrate (Sr(NO3)2) and titanium tetra isopropoxide (TTIP) were dissolved in ethanol solvent. Sample purity, elemental compositions and surface morphology were characterized using x-ray diffraction (XRD), energy dispersive x-ray (EDX) and scanning electron microscopy (SEM). XRD analysis showed that the synthesized SrTiO3 thin layer at 200oC for 24 hours with the addition of CTAB and TBA had intensity peaks that mathced the SrTiO3 standard (ICSD #94573) with perovskite structure. This result was supported by the XRD pattern of the sample powder. The EDX spectrum showed that titanium and oxygen were in the sample, but the presence of strontium was not found, due to its weak intensity. Based on the SEM image, the morphology seen is distributed equally and the grain size is rather smaller in the sample with the addition of CTAB and TBA.